2018
DOI: 10.1016/s2215-0366(18)30090-7
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of discontinuation from antipsychotic maintenance following first-episode schizophrenia and related disorders: a 10 year follow-up of a randomised, double-blind trial

Abstract: Food and Health Bureau, Research Grants Council of Hong Kong, and AstraZeneca.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
95
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(101 citation statements)
references
References 32 publications
1
95
0
1
Order By: Relevance
“…Yet, the first study with a long follow-up time by Wunderink and colleagues reported better outcomes after 7 years with early discontinuation in terms of symptomatic and functional remission compared to maintenance treatment [11]. The recent study conducted by Hui and colleagues [13] could not replicate this finding, as they found a higher risk of poor clinical outcome in the discontinuation group compared to the maintenance group when evaluating long-term clinical outcome at 10 years. This underlines the importance of additional long-term cohorts to systematically investigate the effects of the two strategies on different outcomes.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Yet, the first study with a long follow-up time by Wunderink and colleagues reported better outcomes after 7 years with early discontinuation in terms of symptomatic and functional remission compared to maintenance treatment [11]. The recent study conducted by Hui and colleagues [13] could not replicate this finding, as they found a higher risk of poor clinical outcome in the discontinuation group compared to the maintenance group when evaluating long-term clinical outcome at 10 years. This underlines the importance of additional long-term cohorts to systematically investigate the effects of the two strategies on different outcomes.…”
Section: Discussionmentioning
confidence: 97%
“…The follow-up of the Wunderink [12] study demonstrated that, after 7 years, patients in the original discontinuation condition experienced twice the functional recovery rate (40.4%) in comparison to those on maintenance treatment (17.6%) [11]. However, the recent study by Hui and colleagues [13] also investigating the effects of early discontinuation on long-term clinical outcome at 10 years was in strong contrast with the Wunderink [12] finding, as they reported a higher risk of poor clinical outcome in the discontinuation group compared to the maintenance group (respectively 39% versus 21%). Poor clinical outcome was defined by persistent positive symptoms of psychosis, treatment-resistant psychosis, or death by suicide.…”
Section: Discontinuation Versus Maintenance Therapy: Functional Recoverymentioning
confidence: 96%
See 2 more Smart Citations
“…9,10 Antipsychotic monotherapy is the evidence-based and recommended treatment regimen for both acute symptom exacerbation 4 and for maintenance treatment to prevent future symptom relapse. 11,12 There is no evidence to support monotherapy with pharmaceutical compounds other than antipsychotics. A simplified version of a treatment guideline for use of antipsychotics in schizophrenia is shown in Figure 2.…”
Section: Pharmacological Treatment Of Schizophreniamentioning
confidence: 99%